Synthesis of a hierarchical SiO2/Au/CeO2 rod-like nanostructure for high catalytic activity and recyclability1. Issue 44 (16th May 2015) - Xu, Yuanmei; Zhang, Yiwei; Zhou, Yuming; Zhang, Zewu; Xiang, Sanming; Sheng, Xiaoli; Wang, Qianli; Zhang, Chao
<x xml:space="preserve">Abstract</x> Uniform hierarchical SiO2/Au/CeO2 rod-like nanostructures were successfully fabricated by combining three individual synthesis steps, in which sub-5 nm gold nanoparticles (Au NPs) were coated with a mesoporous CeO2 shell.